Governance in Banks: Does the Role of Monitoring and Control Mechanisms Differ? - Rahim, MA; Rahman, ARA (Acad Conferences Ltd, 2024)
Corporate scandals have been identified as one of the major causes for the failures and weak implementation of corporate governance. In-depth explanation is needed by the shareholders and public i.e., stakeholders as the corporate difficulties and failures all over the world indicated that something is wrong with the implementation in terms of the governance aspects. Board of directors (BOD), chief executive officer (CEO) and the management are the key players in the corporation and they are the ones responsible for the failures as they are in the capacity to monitor and control the corporation. Theoretically, governance may provide ways and solutions in minimizing conflict of interest among parties and also in improving corporation performance. Indeed, corporate governance is essential to ensure smooth running of the business. Nevertheless, business difficulties and failures are still happening around the world. Financial industry also cannot escape from this particular problems and challenges. They play a vital role in supporting economic growth in every country. Therefore, the review of corporate governance codes and literatures from corporation as well as Islamic bank will be used as primary sources for discussion. The objective of this paper is first, to highlight the role of monitoring and control mechanisms of governance for corporation as general i.e., the role of board of directors in emphasizing theirs' duties, responsibilities and functions from governance codes and literatures. Secondly, to describe governance requirements for Islamic banks and finally, to highlight the significant differences between the role of monitoring and control mechanisms of governance for Islamic banks as compared to corporations and conventional banks. This review on literatures and governance guidelines (codes, rules, regulations and frameworks) offers significant theoretical contributions. Firstly, the review provides a comprehensive view on corporate and Shari'ah governance requirements for Islamic banks from the perspective of monitoring and control mechanisms. Secondly, this discussion would be able to highlight the additional governance requirements for the key players in the Islamic banks.